Experiences in Poplar Cultivation Outside Forests - Dalal, S. S.; Trigotra, R. C. (Indian Forester, 1983)
Cultivation of poplars has a well defined scope in lans outside State forests in Haryana and similar other intensively cultivated States lacking natural forests. Poplar plantations are a step in the rlght direction to meet the acute shortage of wood. Roads, canals and farm lands are important sites outside traditional forests where poplar cultivation can be taken up. Roads do not provide ideal sites because of cattle damage and lack of proper irrigation. Canal sites are well suited for introdultion of Populus deltoides G-3. The planting spot along canals should follow the seepage line of the embankment and therefore, the sites have to be selected with reference to the depth of seepage lines. Farm lands provide ideal sites for this species for raising plantations in rows along field boundaries and also in integration with agriultural crops. Sugar-cane is the ideal companion crop for growth of Populus deltoides G-3. Loam and silt loam are best suited for optimum growth. Even mild alkali and satinity reduce. Survival perrentage and growth. Intensive soil management h needed for optimum production. Hand watering is a wasteful and Ideffective practice. A farming system using poplars and crops appears to be well suited in intensively cultivated areas. Planned research is required to promote development of poplars. Clones for water logged and alkali soils need to be developed. Proper machinery and equipment are required to drill deep holes. P. deltoides G-3 is very exacting species and great care is needed to select poplar site. Spacing is of not much serious consideration for row planting but needs careful consideration when poplars are grows with crops in block plantations.